2022
DOI: 10.1063/5.0118861
|View full text |Cite
|
Sign up to set email alerts
|

Experimental base flow modification on a swept wing using plasma forcing

Abstract: This work experimentally investigates plasma actuator (PA) forcing effects on the base flow and developing crossflow (CF) instabilities in a swept wing boundary layer. Spanwise-invariant plasma forcing near the leading edge is configured according to the Base Flow Modification (BFM) strategy. A simplified predictive model is constructed by coupling an experimentally-derived plasma body force and Linear Stability Theory and is used to infer the stability characteristics of the boundary layer subject to BFM. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
(56 reference statements)
1
1
0
Order By: Relevance
“…Reconciling previous studies of Yadala et al, 24 Serpieri et al, 8 and Peng et al 41 as well as the current experiment, the stochastic PAinduced disturbances at both low and high frequencies can potentially damage the PA effectiveness for transition delay, at least within the context of BFM. For instance, to achieve the BFM control, the PA generally requires high power input and needs to be positioned close to the leading edge in order to favorably manipulate the CF component.…”
Section: B a Comment On Bfm Efficacysupporting
confidence: 87%
See 1 more Smart Citation
“…Reconciling previous studies of Yadala et al, 24 Serpieri et al, 8 and Peng et al 41 as well as the current experiment, the stochastic PAinduced disturbances at both low and high frequencies can potentially damage the PA effectiveness for transition delay, at least within the context of BFM. For instance, to achieve the BFM control, the PA generally requires high power input and needs to be positioned close to the leading edge in order to favorably manipulate the CF component.…”
Section: B a Comment On Bfm Efficacysupporting
confidence: 87%
“…The overall transition advancement reported in the present study further highlights the detrimental effects of PA-induced unsteady disturbances and partially resolves the conundrum regarding the effects of unsteady forcing within the context of the BFM method. In the work of Peng et al, 41 the BFM-based PA was found to essentially impose two effects into the boundary layer. One is to weaken stationary CF instabilities (i.e., the intended BFM action), while the other is to enhance unsteady instabilities.…”
Section: Pa Effect On Transition Topology and Locationmentioning
confidence: 99%